AUDIT COMMITTEE FEATURES, SUSTAINABILITY DISCLOSURE, AND CORPORATE PERFORMANCE IN CHARLOTTE FINANCIAL SERVICE COMPANIES - Mohammed Almashhadani; Hasan Ahmed Almashhadani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This study delves into the intricate relationships between Audit Committee (AC) characteristics, sustainability disclosure standards, and corporate performance within the domain of Charlotte's Financial Services Companies. The primary objective is to investigate the complex interplay between AC attributes and the extent of sustainability-related data dissemination among financial entities based in Charlotte. Leveraging a comprehensive dataset spanning 2016 to 2020, covering 537 organizations, the study endeavors to unearth the fundamental mechanisms that underlie the connection between AC characteristics and sustainable disclosure practices. The findings of this study hold significant potential for shedding light on sustainability disclosure practices within Charlotte's financial sector. The central claim posits that robust ACs, emblematic of effective governance processes, may serve as conduits for elevating sustainability disclosure standards. This study introduces a pioneering paradigm, bridging the pivotal role of audit committee characteristics with sustainability disclosure requisites and corporate performance. Empirical support underpins the hypothesis of a positive association between select AC characteristics and the extent of sustainability disclosure. These findings provide actionable insights for managers and practitioners to cultivate specialized governance approaches that bolster sustainable disclosure, ultimately enhancing overall business well-being. By elucidating the intricate interplay between AC characteristics, sustainability disclosure, and company performance in the unique context of Charlotte's Financial Services Companies, this study advances our current understanding and adds to the growing body of research in corporate governance and sustainability strategies. The implications extend beyond Charlotte, offering a conceptual blueprint for fostering sustainable practices through effective governance structures in the financial services industry.